Mind Mapping Based Creative Problem Solving: Train The Creative Thinking Skills of Vocational School Students in Physics Learning - Devi Meiarti; Ellianawati Ellianawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
This study aims to train the creative thinking skills of vocational school students in physics learning by implement the mind mapping based creative problem-solving. This study used experimental methods with one-shot case study design. The population of this study was class X SMK Pelayaran Wira Samudera Semarang. The sample was 30 students selected by purposive sampling technique. The instrument used in this study was student discussion sheets and four items of essay tests. Each item essay test represents an indicator of creative thinking skills. There are learning media used to support learning activities such as powerpoint, Macromedia Flash, and students’ discussion sheets. The results showed the average creative thinking skill of students in physics learning was 58.33% in the sufficient categorized. The highest percentage of that result found on fluency indicator and the lowest found on elaboration indicator. These can conclude that students’ creative thinking skills can trained by implementation of mind mapping based creative problem solving, but not optimally.